Virtual reality and neuropsychology: a cognitive rehabilitation approach for people with psychiatric disabilities - Marques, A. (2022)
This pilot-study evaluated the feasibility of a 9 month Cognitive Rehabilitation Program – using Virtual Reality and the Integrated Psychological Therapy (IPT) – to improve cognitive functioning in people with schizophrenia. In order to assess the program it was applied (pre and post) the WCST, WAIS-III sub-tests, Stroop Test, and The Subjective Scale to Investigate Cognition in Schizophrenia. Results identified significant differences (p<0.05) between pre and post tests in the subjective and objective assessed cognitive dimensions. The results point out that virtual reality technology and IPT may be a significant resource and intervention methodology in the cognitive remediation of people with psychiatric disabilities.